Cultures of Innovation of the African Poor. Common Roots, Shared Traits, Joint Prospects? On the Articulation of Multiple Modernities in African Societies and Black Diasporas in Latin America - Dirk Kohnert (German Institute of Global and Area Studies (GIGA), 2006)
The globalized Western culture of innovation, as propagated by major aid institutions, does not necessarily lead to empowerment or improvement of the well-being of the stakeholders. On the contrary, it often blocks viable indigenous innovation cultures. In African societies and African Diasporas in Latin America, cultures of innovation largely accrue from the informal, not the formal sector. Crucial for their proper understanding is a threefold structural differentiation: between the formal and informal sector, within the informal sector, according to class, gender or religion, and between different transnational social spaces. Different innovation cultures may be complementary, mutually reinforcing, or conflicting, leading in extreme cases even to a 'clash of cultures' at the local level. The repercussions of competing, even antagonistic agencies of innovative strategic groups are demonstrated, analyzing the case of the African poor in Benin and the African Diasporas of Brazil and Haiti. – – Die globalisierte westliche Innovationskultur, wie sie von den großen Entwicklungshilfeinstitutionen propagiert wird, führt nicht notwendigerweise zur Verbesserung der Lebensbedingungen der Armen. Sie blockiert im Gegenteil oft wertvolle Ansätze endogener kultureller Innovationen. In afrikanischen Gesellschaften und in der Afrikanischen Diaspora Lateinamerikas entstehen Innovationskulturen überwiegend im informellen, nicht im formellen Sektor. Diese Innovationskulturen weisen eine dreifache strukturelle Differenzierung auf: zwischen formellem und informellem Sektor, innerhalb des informellen gemäß sozialer Schichtung, Geschlecht oder Religion sowie zwischen transnationalen sozialen Räumen. Diese unterschiedlichen Innovationskulturen können sich gegenseitig ergänzen und verstärken oder aber auch bekämpfen, was in Extremfällen bis hin zum 'Kampf der Kulturen' auf lokaler Ebene führt. Die Auswirkungen dieser konkurrierenden oder antagonistischen Handlungsstrategien innovativer strategischer Gruppen werden an Hand von Fallstudien der Armen in Benin und in der Afrikanischen Diaspora Brasiliens und Haitis aufgezeigt.
Keywords: O31; Z1; E26; Z12; Z13; O57; 300; economic development; cultural change; innovations; social structure; African Diaspora; Benin; Brazil; Haiti; Entwicklung; Innovation; Informeller Sektor; Sozialer Wandel; Armutspolitik; Sozialstruktur; Gesellschaft; Schwarze; Benin; Brasilien; Haiti